The role of interleukin-6 in pathogenesis of chronic periapical lesions - Popović Jelena; Cvetković Tatjana; Džopalić Tanja; Nikolić Marija; Mitić Aleksandar; Barac Radomir; Živković Slavoljub (Serbian Medical Society - Dental Section, Belgrade, 2018)
Introduction Cytokine network plays an important role in pathogenesis of chronic periapical lesions. The aim of this study was to determine the concentration of interleukin-6 (IL-6) in tissue homogenates of human periapical lesions and correlate its levels with symptomatology and size of the lesions. Materials and Methods 93 samples of chronic periapical lesions were obtained after extraction of teeth. Samples were divided according to the clinical presentation as symptomatic and asymptomatic, and according to the size as large and small. The concentration of IL-6 was analyzed using ELISA. Results Statistically significant difference in IL-6 concentration was observed in symptomatic lesions compared to asymptomatic (p<0.001). Analysis showed statistically higher concentration in large symptomatic lesions compared to large asymptomatic lesions (p<0.001), and in small symptomatic lesions compared to small asymptomatic (p<0.05). Higher production of IL-6 was observed in large lesions compared to small but this difference was not statistically significant. Conclusion Higher concentration of IL-6 in lesions with expressed clinical symptoms as well as in large lesions indicates that IL-6 is an important factor responsible for the progression of lesions and bone resorption.